Propostas e discussões para o ensino de astronomia nos 1º e 2º ciclos do nível fundamental e na educação de jovens e adultos - Queiroz, Alex Sander Barros (2005)
This work aims to propose and to discuss methodologies and practical activities for Astronomy teaching in the 1st and 2nd cycles of the primary education and in the adult education. The proposals presented here were applied to students from the metropolitan region of Natal (RN), including students of the called normal education (formerly magisterial education) and of the undergraduate formation in pedagogy at the Instituto de Formação Superior Presidente Kennedy , and also, in particular, to teachers and students of public municipal school Escola Municipal Djalma Maranhão at the district of Felipe Maranhão II, also analyzing some didactic books used by these institutions. Several elements which we confronted with during this didactic-pedagogical experience were systematized, indicating principles, contents, reflections and procedures related to Astronomy teaching to students of those levels of education. Doing this we aim to make such an experience accessible to those interested in developing a similar approach involving the themes treated here as well as other ones related to Astronomy for those levels of education. The resources and practices implemented here aim to contribute to the effective realization of an interdisciplinary and contextualized education according to orientations proposed by the Parâmetros Curriculares Nacionais (Brazilian National Curricular Guidelines). In order to guarantee a broad accessibility to what we propose in this work, we intend to make available in printed form and also in an Internet page the procedures, instruction materials and texts we developed